Peningkatan Kesejahteraan Melalui Pemberdayaan Masyarakat Pesisir Berbasis Teknologi Sebagai Upaya Memperkuat Keamanan Maritim di Indonesia - I Wayan Yuliarta; Hayatul Khairul Rahmat (Jurnal Dinamika Sosial Budaya, 2021)
Indonesia as the largest marine mega-biodiversity in the world makes Indonesia very important to strengthen its maritime security by empowering coastal communities so that the welfare of the community can be achieved. The purpose of this paper is to explain the improvement of welfare through empowerment of coastal communities as an effort to strengthen maritime security in Indonesia. This paper uses a literature research method with a content analysis approach. The findings of this study are that community involvement is needed in empowerment programs that are not only limited to implementing the program, but also involved in the formulation and creation of the program so that the community feels responsible for program implementation and is motivated so that the program runs well. The hope is that with community involvement in efforts to empower technology-based coastal communities, it will take part in supporting Indonesia's maritime security and also improve the welfare of these communities.